Age-Related Macular Degeneration in the Aspect of Chronic Low-Grade Inflammation (Pathophysiological ParaInflammation). (19th August 2014) - Nita, Małgorzata; Grzybowski, Andrzej; Ascaso, Francisco J.; Huerva, Valentín
Abstract : The products of oxidative stress trigger chronic low-grade inflammation (pathophysiological parainflammation) process in AMD patients. In early AMD, soft drusen contain many mediators of chronic low-grade inflammation such as C-reactive protein, adducts of the carboxyethylpyrrole protein, immunoglobulins, and acute phase molecules, as well as the complement-related proteins C3a, C5a, C5, C5b-9, CFH, CD35, and CD46. The complement system, mainly alternative pathway, mediates chronic autologous pathophysiological parainflammation in dry and exudative AMD, especially in the Y402H gene polymorphism, which causes hypofunction/lack of the protective complement factor H (CFH) and facilitates chronic inflammation mediated by C-reactive protein (CRP). Microglial activation induces photoreceptor cells injury and leads to the development of dry AMD. Many autoantibodies (antibodies against alpha beta crystallin, alpha-actinin, amyloid, C1q, chondroitin, collagen I, collagen III, collagen IV, elastin, fibronectin, heparan sulfate, histone H2A, histone H2B, hyaluronic acid, laminin, proteoglycan, vimentin, vitronectin, and aldolase C and pyruvate kinase M2) and overexpression of Fcc receptors play role in immune-mediated inflammation in AMD patients and in animal model. Macrophages infiltration of retinal/choroidal interface acts as protective factor in early AMD (M2 phenotype macrophages); however it acts as proinflammatory and proangiogenic factor in advanced AMD (M1 and M2 phenotype macrophages).